The effect of a multicomponent multidisciplinary bundle of interventions on sleep and delirium in medical and surgical intensive care patients1. (June 2014) - Patel, J.; Baldwin, J.; Bunting, P.; Laha, S.
Summary Sleep deprivation is common among intensive care patients and may be associated with delirium. We investigated whether the implementation of a bundle of non‐pharmacological interventions, consisting of environmental noise and light reduction designed to reduce disturbing patients during the night, was associated with improved sleep and a reduced incidence of delirium. The study was divided into two parts, before and after changing our practice. One hundred and sixty‐seven and 171 patients were screened for delirium pre‐ and post‐intervention, respectively. Compliance with the interventions was > 90%. The bundle of interventions led to an increased mean (SD) sleep efficiency index (60.8 (3.5) before vs 75.9 (2.2) after, p = 0.031); reduced mean sound (68.8 (4.2) dB before vs 61.8 (9.1) dB after, p = 0.002) and light levels (594 (88.2) lux before vs 301 (53.5) lux after, p = 0.003); and reduced number of awakenings caused by care activities overnight (11.0 (1.1) before vs 9.0 (1.2) after, p = 0.003). In addition, the introduction of the care bundle led to a reduced incidence of delirium (55/167 (33%) before vs 24/171 (14%) after, p < 0.001), and less time spent in delirium (3.4 (1.4) days before vs 1.2 (0.9) days after, p = 0.021). Increases in sleep efficiency index were associated with a lower odds ratio of developing delirium (OR 0.90, 95% CI 0.84–0.97). The introduction of an environmental noise and light reduction programme as a bundle of non‐pharmacological interventions in the intensive care unit was effective in reducing sleep deprivation and delirium, and we propose a similar programme should be implemented more widely.